Dynamics of Halal Certification Application in Medicinal Products: Comparative Study of Islamic Law and Positive Law - Rafianti, Fitri; Asmuni, Asmuni; Jamil, Jamil (SASI, 2023)
Introduction: This article wants to explain the dynamics of halal certification and labeling in Indonesia in a review of positive law and Islamic law.Purposes of the Research: The research objective is to answer the dynamics of halal certification and labeling from the perspective of positive law and Islamic law.Methods of the Research: This research uses a qualitative method with a normative legal approach. Data is obtained through observations, in-depth interviews, literature reviews, and documentation.Results of the Research: This research shows that the implementation of halal certification according to Law Number 33 of 2014 on various products, including medication, cannot be separated from the role of political will and synergy among various parties. From the perspective of positive law, halal certification is a legal obligation, while from the perspective of Islamic law, halal certification is part of the obligation to ensure that products consumed by Muslims are guaranteed halal.